Asuhan Kebidanan Continuity of Care Ny. K Umur 28 Tahun G2P1A0 di PKM X dengan Kehamilan Letak Bokong - Suci Rohandayani; Ari Widyaningsih (Universitas Ngudi Waluyo, 2024)
Continuity of care is the provision of obstetric care starting from pregnancy, childbirth, postpartum, neonate to deciding to use family planning. This aims to help, monitor, and detect the possibility of complications that accompany the mother and baby from pregnancy to the use of birth control. The midwifery care method at PKM X is through home visits by providing counseling according to the needs of mothers. Midwifery care given to Mrs.